X‐linked BCOR variants identified in Chinese Han patients with congenital heart disease. (22nd November 2022) - Suo, Mei‐Jiao; Chen, Wei‐Cheng; Xu, Zi‐Qing; Tian, Gui‐Xiang; Li, Ting; Li, Ping; Sheng, Wei; Huang, Guo‐Ying; Ma, Xiao‐Jing
Abstract: Background: Congenital heart disease (CHD) frequently manifests as a complex phenotype and approximately one‐third of cases may be caused by genetic factors. BCOR, an X‐linked gene encoding the corepressor of BCL6, has been demonstrated to be closely involved in human heart development. However, whether BCOR variants represent the genetic etiology underlying CHD needs further investigation. Methods: We performed whole exome sequencing on CHD nuclear families and identified a candidate gene, BCOR, by robust bioinformatic analysis and medical literature searches. Targeted DNA sequencing of the candidate gene was conducted and then the association between variants and the risk of developing CHD was analyzed. The effects of BCOR mutations on gene expression, localization, protein interaction, and signaling pathways were evaluated in vitro . Results: We identified a BCOR hemizygous missense variant (c.1448C>T, p.Pro483Leu) in a male proband presented with CHD/heterotaxy. Sanger sequencing confirmed that this variant was inherited from his asymptomatic mother. Interestingly, through literature searches, we observed another novel BCOR hemizygous missense variant (c.1619G>A, p.Arg540Gln) in a CHD patient with heterotaxy, supporting the pathogenic evidence of BCOR variants. Functional experiments conducted in vitro revealed that the variant p.Pro483Leu altered the subcellular localization of BCOR protein, disrupted its interaction with BCL6, and significantly promoted cell proliferation, whereas the variant p.Arg540Gln displayed no obvious effects. Nevertheless, transcriptional analysis revealed that down‐regulation of BCOR substantially enhanced the activities of mitogen‐activated protein and phosphoinositide 3‐kinase‐AKT signaling pathways, which are closely attributed to heart development. Targeted sequencing of 932 sporadic CHD patients enriched nine variants of BCOR predicted as likely rare and damaging and a septal defect was present in 81.8% (9/11) of them, including the two probands, which was consistent with the possible phenotype caused by BCOR defects. Conclusions: The findings of the present study indicate that variants in BCOR may predispose individuals to CHD in the Chinese Han population. Abstract : We identified two BCOR missense variants (c.1448C>T and c.1619G>A) in two nuclear families. Functional experiments performed in vitro revealed the pathogenicity of two variants. Targeted sequencing in congenital heart disease (CHD) patients enriched nine variants of BCOR predicted as likely rare and damaging and the septal defect occupied the vast majority of cardiac‐related phenotypes. Our findings indicated that variants in BCOR may predispose individuals to CHD in the Chinese Han population.